PENGARUH MODEL PEMBELAJARAN STAD BERBANTUAN KUIS INTERAKTIF WORDWALL TERHADAP HASIL BELAJAR IPAS SISWA KELAS III SD - Mela Astriani; Magdad Hatim; Ida Suryani (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
This study aimed to determine the effect of the Student Teams Achievement Division (STAD) learning model assisted by Wordwall interactive quizzes on the science and social studies (IPAS) learning outcomes of third-grade students at SD Negeri 127 Palembang on the topic of Energy Around Us. The study was motivated by the persistently low learning outcomes in IPAS, attributed to teacher-centered instruction and limited use of varied learning models or media. This study employed a quantitative approach with a quasi-experimental method, specifically a Non-Equivalent Control Group Design. The sample was determined using a Cluster Random Sampling technique, consisting of an experimental class and a control class. Learning outcome data were collected through pretest and posttest assessments using a validated and reliable multiple-choice test instrument, which were then analyzed using normality tests, homogeneity tests, and an independent samples t-test at a significance level of 0.05. The results showed that the experimental class, which implemented the STAD model assisted by Wordwall interactive quizzes, experienced a greater improvement in learning outcomes than the control class, with a statistically significant difference. These findings indicate that the STAD learning model assisted by Wordwall interactive quizzes has a significant effect on improving IPAS learning outcomes among third-grade elementary school students, and can therefore serve as an innovative alternative learning model for teachers to enhance the quality of IPAS instruction in elementary schools. ABSTRAK Penelitian ini bertujuan untuk mengetahui pengaruh model pembelajaran Student Teams Achievement Division (STAD) berbantuan kuis interaktif Wordwall terhadap hasil belajar IPAS siswa kelas III SD Negeri 127 Palembang pada materi Energi di Sekitar Kita. Penelitian ini dilatarbelakangi oleh masih rendahnya hasil belajar IPAS siswa akibat pembelajaran yang berpusat pada guru dan minimnya penggunaan model maupun media pembelajaran yang variatif. Metode yang digunakan adalah pendekatan kuantitatif dengan desain eksperimen semu (quasi experimental), yaitu Non-Equivalent Control Group Design. Sampel penelitian ditentukan menggunakan teknik Cluster Random Sampling, terdiri atas kelas eksperimen dan kelas kontrol. Data hasil belajar dikumpulkan melalui pretest dan posttest menggunakan instrumen tes pilihan ganda yang telah teruji validitas dan reliabilitasnya, kemudian dianalisis melalui uji normalitas, uji homogenitas, dan uji-t pada taraf signifikansi 0,05. Hasil penelitian menunjukkan bahwa kelas eksperimen yang menerapkan model STAD berbantuan kuis interaktif Wordwall mengalami peningkatan hasil belajar yang lebih tinggi dibandingkan kelas kontrol, dengan perbedaan yang signifikan secara statistik. Dengan demikian, dapat disimpulkan bahwa model pembelajaran STAD berbantuan kuis interaktif Wordwall terbukti berpengaruh signifikan terhadap peningkatan hasil belajar IPAS siswa kelas III sekolah dasar, sehingga dapat dijadikan alternatif model pembelajaran yang inovatif bagi guru dalam meningkatkan kualitas pembelajaran IPAS di sekolah dasar.